Public Resistance to Cryptocurrency and Its View From the Islamic Perspective - Ashal, Farid Fathony (Sharia and Law Faculty, 2024)
Cryptocurrency appeared amid digital technology's growth tremendously, offering fast, transparent, auditable, and secure features. However, its presence and status in Islamic law are still debatable among the Community. Cryptocurrency is based on blockchain and has decentralized finance, contrary to the current conventional system, namely central banks. The purpose of this study is to see community resistance over cryptocurrencies and its views on the Islamic perspective. This study is qualitative with a phenomenology approach. Data sources were obtained through in-depth interviews and structured ones. The analysis carried out in this study used the maqashid sharia approach, fiqh rules, and ushul fiqh. The result of this study showed that the concept of decentralized finance has yet to be able to take over the role of central banks. The majority of perspectives provided by the ulama, who were consulted as primary sources in this research, maintain the belief that cryptocurrency remains an unreliable medium of exchange and a risky long-term asset.